Diagnosis and treatment of congenital megalodolichocolon - Ergashev, N; Nazarov, Nurali (Medical and Health Science Journal, 2011)
The results of diagnosis and treatment of congenital anomalies of the colon in 107 children were examined. Twenty nine patients underwent surgical correction: 24 intra-resection of the colon by Rehbein and 5 abdominoperineal rectoplasty by Soave-Lenushkin and Soave-Boley. In extending of colon in combination with megarectum the preference is given to Soave operation and its modifications.
Keywords: kolon; megakolon; dítě; předškolní dítě; Colorectal Surgery; výsledek terapie; nemoci tlustého střeva; Adolescent; Colon; lidé; Intestinal Obstruction; kolorektální chirurgie; Treatment Outcome; Colonoscopy; Colonic Diseases; Child, Preschool; střevní obstrukce; kolonoskopie; Megacolon; Child; mladiství; Humans